Focusing on the Place Model for Optometrists - Julie F McClelland; Karen Breslin (Education Sciences, 2019)
Background: The Place Model was developed in order to conceptualize the various roles and career pathways of the teaching profession. It can be used to evaluate long-term professional career trajectories and to encourage the student-teacher to visualize their future personal and professional development. Methods: In the present study, the Place Model has been applied to the Optometric profession. The four categories of the place model have been discussed in terms of Optometry and a survey of undergraduate Optometrists highlights the perception of the model amongst pre-qualified professionals. Results: The majority of participants placed qualified optometrists in the Professional area on the Place Model (87%, n = 88) with the remainder placing qualified optometrists in the De-Professional area on the Place Model (13%, n = 13). There was no statistically significant difference between responses from male and female participants (t-test, p = 0.38). There was also no statistically significant difference between responses from participants in year 1, 2 or 3 of their undergraduate program (one-way analysis of variance [ANOVA], p = 0.10). Conclusion: The Place Model may be an opportunity to discuss with Optometry students their future career pathways and to ensure that we maintain a highly skilled and caring profession that provides high quality eyecare for the public.